Socialist trends in Indian national movement : being a study of the Congress Socialist Party - Girja Shankar, 1935- (Meerut : Twenty-First Century Publishers, 1987)
Covers the period, 1934-1948.
Includes index.
Bibliography: p. [342]-353.
Keywords: Congress Socialist Party -- History; Socialism -- India -- History; Nationalism -- India -- History; India -- Politics and government -- 1919-1947.